Institutionalizing Ethics in Institutional Voids: Building Positive Ethical Strength to Serve Women Microfinance Borrowers in Negative Contexts - Chakrabarty, Subrata (Journal of business ethics, 2014)
This study examines whether microfinance institutions (MFIs) that serve women borrowers at the base of the economic pyramid are likely to adopt a written code of positive organizational ethics (POE). Using econometric analysis of operational and economic data of a sample of MFIs from across the world, we find that two contextual factors—poverty level and lack of women’s empowerment—moderate the influence of an MFI’s percentage of women borrowers on the probability of the MFI having a POE code. MFIs that serve more women borrowers are more likely to adopt a POE code, especially in negative contexts (where women borrowers face poverty and disempowerment and are therefore susceptible to abuse). This study provides evidence that MFIs can build positive ethical strength in negative contexts.